Electrochemical Sensing of Dissolved Hydrogen in Aqueous Solutions as a Tool to Monitor Magnesium Alloy Corrosion. Issue 5 (5th March 2013) - Kuhlmann, Julia; Witte, Frank; Heineman, William R.
Abstract Magnesium and its alloys have been the focus of the development of biodegradable metallic implant materials for years. Since water is reduced to form hydrogen gas during their corrosion, the amount and rate of hydrogen evolution, and therefore the dissolved hydrogen, could be used as an indicator to monitor and compare the corrosion. Here we report on a commercially available Clark‐Type amperometric microsensor and a simple potentiometric sensor for hydrogen to monitor the corrosion of a magnesium alloy in aqueous solutions. The sensors were compared using rare‐earth containing Mg alloy discs (Mg with 4 % Y, 2 % Nd, 0.5 % Ga, 0.5 % Dy) immersed in phosphate buffered saline (pH 7.4) and 3.5 % NaCl.